The Problem of Being in Heidegger - Pathak, Chintamani (My University, 1972)
The thesis is an attempt to a critical exegesis of Heidegger's problem of Being. It is "critical" in so far as it seeks to situate the question of Being with critical awareness of the positivistic and empirical ontology where a this is said "to be" only if it is pointable out there in physical space and time. It attempts to show that for Heidegger Being is not a this but a meaning-giving (Sinngebung) question - a question which becomes concrete from the fact of man's being "there" (da) in the world. Man's being-there (da-Sein) makes the question of the meaning of Being possible. In so far as the thesis attempts to clarify the horizon within which Heidegger's questioning makes its intended sense, it is "exegetical". A critical exegesis of a philosophical view requires a proper mapping of the conceptual framework within which a certain philosophical thinking grows, moves and has its being. Wthout "a proper mapping of the conceptual framework", and boundary-setting philosophies look upon one another with fear and suspicion. A felt necessity of "boundary-setting" guides Heidegger to lay the foundation of fundamental phenomenological ontology where "Being" itself becomes a "matter of thinking" (die Bache des Denkens).
Heidegger's question is not "What is Being?" but how to question, think and speak what Being is. The what of Being in other words is a matter of how to understand the question of Being and speak what it is. It is the question of thinking and speaking that Being is (es gibt Beln). Since philosophy here is concerned equally with the method and with the sUbject-matter, the problem of Being necessarily brings about the problem of the logos of Being. The method and the theme of philosophY intercede and constitute the unity of Heidegger's thought. The central theme of Heidegger's thought - the problem of Being - underlies, grows and culminates like a dialectical process through phenomenology, thinking and language.
The exegesis of the inner dialectic of the theme and method requires its treatment in two parts. The first part of the thesis is concerned with the clarification of basic philosophical categories aimed to clarify the question about the meaning of Being. Its aim is to clarify Heidegger's fundamental philosophical approach. A discussion of these categories - like "the problem of ontological difference", "forgetfulness of Being" and "clearing-ground" forms the subject-matter of the first part. The second part deals with the problem of the method, or the how "what Being is" can be said or shown. An understanding of "what is the question about the meaning of Being" thus requires an understanding of what Heidegger means by phenomenology, thinking and language. It is our aim to reconcile the question of phenomenology, thinking and language with Heidegger's basic question about the meaning of Being. The thesis however does not claim to say the last word on the problem. It is rather a synoptic attempt to point out the fundamental horizon of Heidegger's basic question - the question about the meaning of Being.
Keywords: Philosophy; Philosophy